Extended vs non‐extended pelvic lymph node dissection and their influence on recurrence‐free survival in patients undergoing radical cystectomy for bladder cancer: a systematic review and meta‐analysis of comparative studies. (May 2014) - Bi, Liangkuan; Huang, Hai; Fan, Xinxiang; Li, Kaiwen; Xu, Kewei; Jiang, Chun; Liu, Hao; Dong, Wen; Zhang, Simin; Yang, Xiangyun; Lin, Tianxin; Huang, Jian
Abstract : Objective: To compare extended pelvic lymph node dissection (ePLND) with non‐extended pelvic lymph node dissection (non‐ePLND) and assess their influence on recurrence‐free survival (RFS) in patients undergoing radical cystectomy for bladder cancer. Methods: Through a comprehensive search of the PubMed, Embase and Cochrane Library databases in September 2012, we performed a systematic review and cumulative meta‐analysis of all comparative studies assessing the extent of pelvic lymph node dissection (PLND) and its influence on RFS. Results: Six studies with a total of 2824 patients were identified. Overall analysis showed a significantly better RFS rate in patients who had undergone ePLND than in those who had undergone non‐ePLND (hazard ratio [HR]: 0.65; P < 0.001). A subgroup analysis found that, compared with non‐ePLND, ePLND was associated with a better RFS rate for both patients with negative lymph nodes (HR: 0.68; P = 0.007) and those with positive lymph nodes (HR: 0.58; P < 0.001). When stratified by pathological T stage, ePLND provided additional RFS benefits for patients with pT3–4 disease (HR: 0.61; P < 0.001), but not for patients with ≤pT2 disease (HR: 0.95; P = 0.81). Conclusions: The results of this meta‐analysis indicate that ePLND provides a RFS benefit compared with non‐ePLND. On subgroup analysis, ePLND provides better RFS not only for patients who had positive lymph nodes and pT3–4 disease, but also for patients with negative lymph nodes. Two randomized controlled trials on ePLND vs non‐ePLND are awaited which should provide more clinically meaningful results.